STUDI KUAT TEKAN BETON RINGAN STRUKTURALDENGAN PEMANFAATAN KALSIUM KARBONAT (CaCO3), SERBUK BATU APUNG DAN TETES TEBU (MOLASE) - Fauzi, Muhammad; Arumningsih , Dian; Susila, Herman (Civil Engineering, Faculty of Engineering, Universitas Tunas Pembangunan Surakarta, 2025)
This study investigates the potential of incorporating calcium carbonate (CaCO?) as a partial replacement for cement, pumice powder as a substitute for fine aggregates, and molasses as a natural retarding admixture in the development of structural lightweight concrete. The research is motivated by the growing need for sustainable, low-density construction materials that are suitable for seismic regions such as Indonesia. An experimental approach was adopted, involving laboratory testing of compressive strength and density at curing ages of 7, 14, and 28 days. The evaluation criteria were based on the Indonesian National Standard (SNI 2847:2019), which specifies a minimum compressive strength of 17.24 MPa and a maximum density of 1840 kg/m³ for structural lightweight concrete. The experimental results demonstrated that the proposed material combinations successfully met the required standards. The optimum mix composition consisted of 10% CaCO? by weight of cement, 40% pumice powder by total fine aggregate, and 0.2% molasses. Among the tested variations, the BR-40% mixture achieved a compressive strength of 27.03 MPa and a density of 1824 kg/m³, while the BR-50% mixture yielded 24.53 MPa and 1710 kg/m³, respectively. These findings confirm the feasibility of using such innovative materials to produce lightweight concrete with enhanced structural performance and improved sustainability